Using predictive analytics to solve a newsvendor problem / S. Sarifah Radiah Shariff and Hady Hud - Shariff, S. Sarifah Radiah; Hud, Hady (Malaysia Institute of Transport (MITRANS), UiTM, 2023)
Purpose Forecasting accuracy is an ongoing challenge for many companies. The pandemic has resulted in unpredictable customers’ purchasing patterns post-pandemic has rendered heuristic-based forecasting large forecast errors, which leads to poor decision-making. It is debatable whether such behaviour may persist long after the pandemic ends or settle down at a new normal level. The objective of this research is to forecast the daily demand of a perishable product during the new norm post-pandemic, ensuring minimal unsold items are discarded as waste.